The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.2139/ssrn.478022
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Knowledge, Search Locations, and Consumer Choice

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
195
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(205 citation statements)
references
References 35 publications
5
195
1
4
Order By: Relevance
“…According to Balabanis et al (2002), a greater level of direct contact with a country or its products lead to more objective consumer product perceptions. Moorman et al (2004) have shown how subjective knowledge exemplified by product familiarity can affect the quality of consumers' choices by having an influence on where consumers search for information. Cowley and Mitchell (2003) have found that the level of knowledge affects the usage of information; higher levels of knowledge about an object lead to a more efficient use of knowledge about that object.…”
Section: Country-of-origin Evaluationsmentioning
confidence: 99%
“…According to Balabanis et al (2002), a greater level of direct contact with a country or its products lead to more objective consumer product perceptions. Moorman et al (2004) have shown how subjective knowledge exemplified by product familiarity can affect the quality of consumers' choices by having an influence on where consumers search for information. Cowley and Mitchell (2003) have found that the level of knowledge affects the usage of information; higher levels of knowledge about an object lead to a more efficient use of knowledge about that object.…”
Section: Country-of-origin Evaluationsmentioning
confidence: 99%
“…However, knowledge levels and understanding of environmental labels have been found to be 112 low, which could deter adoption of these labels when making food choices (Grunert, et (Moorman, et al, 2004). This leads to substantial 155 correlation between both types of knowledge (Brucks, 1985;Raju, et al, 1995), although this 156 was found to be stronger for products relative to non-products (e.g., financial or medical 157 services) and public relative to private goods (Carlson, et al, 2009 regard to carbon footprint information was shown to increase intentions to purchase products 165 with a lower carbon impact (Wikoff, Rainbolt, & Wakeland, 2012).…”
mentioning
confidence: 99%
“…Past research suggests that subjective knowledge is highly correlated to objective knowledge (Carlson et al 2009;Kwon and Lee 2009;Moorman et al 2004). Subjective knowledge refers to the degree to which consumer perceive how much they know about the product (Brucks 1985;Park et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Subjective knowledge refers to the degree to which consumer perceive how much they know about the product (Brucks 1985;Park et al, 1994). As consumer judgment and decision are largely affected by self-assessed knowledge (Carlson et al 2009;Kwon and Lee 2009;Moorman et al 2004), this study thus adopted subjective knowledge to evaluate product knowledge and measured the construct by using the items from Brucks (1985) and Park et al (1994). The three product knowledge items were: "I feel I am confident in using digital camera/leisure farm information compared to the average consumers", "I feel I am knowledgeable in using digital camera/leisure farm information compared to the average consumers", and "I feel I am confident about my ability to comprehend digital camera/leisure farm information".…”
Section: Methodsmentioning
confidence: 99%